Penentuan ukuran pipa kapiler dengan program aplikasi CapSel Versi 1.0 pada AC trainer unit jenis ekspansi langsung dengan R-410A - I Dewa Made Susila; I Wayan Adi Subagia; I Made Rasta (Journal of Applied Mechanical Engineering and Green Technology, 2022)
The use of air conditioning system currently mostly uses the vapor compression cycle. One such air conditioning machine is a direct expansion type AC. In this type of air conditioner, the air is directly cooled by the refrigerant. Cold air is flowed through the air duct to be entered into the room to be cooled. The refrigerant used is R-410A which does not contain chlorine so it does not cause depletion of the ozone layer because it has an ODP = 0. This direct expansion unit trainer uses an expansion device in the form of a capillary tube and an external equalizer type TXV. To determine the size of the capillary tube on the trainer unit, the direct expansion type uses the CapSel version 1.0 application program. By using the input data for refrigerant type R-134A, refrigeration capacity 2,637.6 Watt (9000 BTU/hour), evaporation temperature 5 °C condensation temperature 47 °C, and return gas temperature 12 °C, the recommended capillary pipe size data is obtained, namely the length of the pipe. capillary 1.47 m with an inner diameter of 2.50 mm. The test was carried out by varying the velocity of the air leaving the airways at high speed (22.3 ft/s) and at low speed (7.9 ft/s). The refrigerant temperature and pressure data are measured at 4 measurement points and the measurement of the electric current entering the system. After processing the data and entering it into the Coolpack application program, the average COP and EER in the low speed position produce a higher price than the high speed position.